Phenotypic and symbiotic characterization of bacteria nodulating Genista saharae in the arid region of Algeria - Djouama, Manel; Foughalia, Abdelhamid; Boulila, Farida; Chala, Adel (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
Twenty bacterial strains had been isolated from root nodules of Genista saharae that grew wild in Biskra and El Oued city (Northeastern Algerian Sahara). This study focused on obtaining isolates of legume nodule bacteria (LNB) from the plant G. saharae and evaluated their effectiveness in forming a symbiotic relationship with the legume species Vigna unguiculata through cross-inoculation. Additionally, the study aimed to identify the successful cross-inoculation group of LNB strains based on their phenotypic characteristics. The growth capacity of isolates under varying salinity conditions [NaCl] and pH levels was investigated using a spectrophotometer (96-microplate reader). The API 20NE and API 20E systems were used to identify the biochemical characteristics of the isolates. In addition, the rhizospheric soil samples from the two study sites were analyzed using standard analytical techniques of soil. All isolates established effective symbioses with Vigna unguiculata, were Gram-negative rods, and were fast-growing. The optimal growth temperature was between 28 °C and 37 °C; some isolates were thermophiles and specifically withstood extreme heat between 45-50 °C. Furthermore, they demonstrated a wide tolerance range to pH (5–10) with salt tolerance ranging from 100 mM to 500 mM. Biochemical results revealed that the isolates assimilated various sources of carbon and nitrogen and displayed numerous enzyme activities. Physicochemical analysis revealed that all the soils were deficient in nutrients and had an alkaline pH. This study enabled us to identify the effective stress-tolerant strains, which could be used in the future to inoculate plants for environmental applications.